P22 Assessing the impact of a telephone clinic to supplement the vetting process for pulmonary rehabilitation (PR) referrals. (12th November 2019) - Brock, L; McDonnell, L; Hogg, L; Dewar, A
Abstract : Introduction and Objectives: Local data shows that only around 60% of PR assessment clinic appointments are attended. Missed appointments delay treatments, increase the cost of care, reduce efficiency and negatively impact relationships between patients and health care professionals. 1 Referrals to our university teaching hospital PR service are received from clinicians in primary, secondary or tertiary care. PR referrals they are vetted against clinical criteria (MRC ≥2 or decreased exercise tolerance and no contraindications) by senior physiotherapists. Our aim was to investigate if supplementing the vetting process with a telephone clinic to assess suitability and engage patients would have any impact on attendance. Methods: Telephone calls were made by a senior physiotherapist and data was collected prospectively over a 7 month period. Patients were deemed as unable to be contacted after three telephone calls were attempted. Results: 199 PR referrals were vetted during this period. Staffing levels meant that 54 patients were vetted without receiving telephone calls. Thirty-five patients were unable to be contacted despite 3 attempts; therefore 117 patients received vetting calls. Conclusions: Patients who received telephone calls were more likely to decline to attend assessment clinic than to not attend the assessment appointment (DNA), this enabled an alternative patient to be booked in their place, and resulted in a lower non-attendance rate for the assessment clinic. Attempted calls took approximately 5 minutes and successful calls took approximately 15 minutes compared to clinic appointments being 1 hour in duration. Patients who could not be contacted had a much higher DNA rate than those we did not attempt to call or those who were successfully called. Further investigation into how best to engage with this group is likely to be beneficial. This patient group was also noted to have a high non-attendance rate in other clinical settings. Reference: McLean SM, et al . Appointment reminder systems are effective but not optimal: results of a systematic review and evidence synthesis employing realist principles. Patient Preference and Adherence 2016;10:479.